2013
DOI: 10.1186/1750-1172-8-113
|View full text |Cite
|
Sign up to set email alerts
|

Importance of therapeutic patient education in ichthyosis: results of a prospective single reference center study

Abstract: BackgroundIchthyoses are a heterogeneous group of rare genodermatoses. Patients and their families face difficulties related to daily care and management that may be aggravated by social isolation.ObjectivesTo evaluate the impact of therapeutic educational programs in improving the knowledge of ichthyosis patients, and their relatives, about their disease.Patients and methodsWe organized a two sessions-program of “know-how” dedicated to the overall management of ichthyoses. These sessions were conducted based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
0
5
0
2
Order By: Relevance
“…In addition, the study demonstrated that the psychological and social aspects of the life of patients with autosomal recessive congenital ichthyoses and their families were affected by this disease ( Abeni et al, 2021 ). Moreover, Dufresne et al (2013) found that therapeutic educational programs in a neutral place (out of routine therapeutic and health care centers) for patients with ichthyoses improved the patients’ and their families’ knowledge and social skills, which could be considered in future studies on Iranian patients with EB. Furthermore, in a study by Sjedianfard et al (2021) on FQoL in patients with pemphigus vulgaris, FQoL was shown to be poorer in families with male patients, older patients, and shorter duration of disease, as well as in lower-educated caregivers.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, the study demonstrated that the psychological and social aspects of the life of patients with autosomal recessive congenital ichthyoses and their families were affected by this disease ( Abeni et al, 2021 ). Moreover, Dufresne et al (2013) found that therapeutic educational programs in a neutral place (out of routine therapeutic and health care centers) for patients with ichthyoses improved the patients’ and their families’ knowledge and social skills, which could be considered in future studies on Iranian patients with EB. Furthermore, in a study by Sjedianfard et al (2021) on FQoL in patients with pemphigus vulgaris, FQoL was shown to be poorer in families with male patients, older patients, and shorter duration of disease, as well as in lower-educated caregivers.…”
Section: Discussionmentioning
confidence: 98%
“…Ни дети, ни их родители зачастую не понимают, как можно предотвратить эти двигательные и сенсорные осложнения. Цель терапевтического образования больных детей состоит в том, чтобы помочь им лучше понять свою болезнь, необходимость выполнения ежедневного ухода за кожей и других процедур для их выживания и комфорта [44,45]. Кожные симптомы оказывают значительное влияние на качество жизни пациентов, но мало что известно о бремени (психологическом, социальном, экономическом, физическом) этого заболевания на семьи пациентов.…”
Section: разделunclassified
“…Educational interventions (‘ichthyosis schools’) may be very useful to improve treatment adherence and lessen fears and misconceptions (LoE 3, GoR D) . Nevertheless, formal and structured multidisciplinary educational programmes have been established in a minority of European countries, and there are very few data evaluating their impact . Patients must be informed about the national patient support groups that exist in many European countries and allow support from other families and sharing of individual experiences (LoE 4, GoR D).…”
Section: Psychosocial Management Communicating the Diagnosis And Genmentioning
confidence: 99%